Założenia europejskiej unii walutowej - Komar, Andrzej (Wydział Prawa i Administracji UAM, 1992)
The author first presents the stages of monetary integration of the EEC countries and against that backround explains in some detail the principles of functioning of the European monetary system. Special attention was paid to the construetion of the European Currency Unit (ECU) and to the accompanying forms of financial and monetary interventions. esides the author points to the shortcomings of the European monetary system and to the ways of seeking the methods of implementing the monetary union. in connection with the above, the author summarizes main theses of Jacques Delors Report of 1989. The main subject-matter of the analysis is the creation of the European monetary union (I Stage; 1 July 1990), and the Economic and Monetary Union Treaty of December 1991. The author refers to the schedule of implementing the II and III stage of the monetary union and discusses the conditions of convergence of economic and financial policy, related to the implementation of the union. Furthermore the author discusses institutional matters (the foundation of the European Monetary Institute the European System of Central Banks, and the European Central Bank) Against that background the author explains the issuance of ECU cerning uniform European currency. The article is concluded with remarks concerning the adjustment of the Polish monetary system to the conditions of the European monetary union.
Assumptions of European Monetary Union